449 Role of neoadjuvant chemotherapy on local control in locally advanced vulvar carcinoma: a single institution experience. (13th November 2020) - Adorni, M; Negri, S; Bazzurini, L; Vecchione, F; Lissoni, A; Buda, A; Landoni, F
Abstract : Introduction: About one third of vulvar carcinoma is diagnosed at an advanced stage and is either surgically unresectable or require pelvic exenteration. Neoadjuvant chemotherapy (NACT) has been introduced to reduce surgical invasivity. In this case series we describe our experience with NACT from January 2000 to December 2018. Methods: This retrospective study analyzes 15 patients affected by locally advanced vulvar carcinoma (FIGO II-IVB) treated with NACT for large tumors (T2-T3) involving the anal sphincter or the urethra. The chemotherapy regimen mainly used a combination of Cisplatin Taxol and Ifosfamide. Clinical data were obtained by reviewing medical, radiological and pathological records. Results: 14 patients completed all the expected cycles of NACT and only 3 presented G3-G4 toxicity. Locally, the treatment resulted in 3 complete responses (20%), 7 partial responses (46.6%), 3 stable diseases (20%) and 2 progressions of disease (13, 3%) (Table 1 ). Excluding the latter, all patients underwent surgery. Among the 9 with urethra involvement before NACT, 2 required a partial urethral amputation, and out of 7 patients with anus involvement 2 required surgery on the digestive tract. Surgical margins were negative in all cases. Of the 13 patients who underwent surgery, 3 had persistent disease and 3 relapsed. The overall median survival was 55 months, with some long survivor patients (figure 1 ). Conclusion: NACT followed by surgery for the treatment of locally advanced vulvar carcinoma is feasible, well tolerated and allows surgical modulation.